Factors Associated with Irrational Antibiotic Use Behaviour among Social Media Users in Thailand - แสงอังศุมาลี ชินวัจน์; ตันติพิวัฒนสกุล กมลวรรณ; ประจักษ์เนตร พรพรรณ; พงษ์ธนานิกร สุญาณี; ทองแท้ ณัฐกานต์ (Journal of Health Science of Thailand, 2024)
The antibiotics are currently less effective as the bacteria adapt to resist the antibiotics, resulting in a lower efficacy affecting drug-resistant bacterial infections. Previous research indicated that improper use of antibiotics triggered one of the significant causes of resistance infection. This study aimed to examine factors related to the irrational use of antibiotics among social media users in Thailand. Quantitative research approach was employed in this study, using a cross-sectional survey. Selfadministered online questionnaires were distributed to 400 respondents who were social media users. The study was conducted between February and April 2021. Data were analyzed using the Chi-square test and Pearson correlation analysis. The study found that gender, education level, reason for using antibiotics, income, and source of antibiotic exposure were significantly related to antibiotic utilization behavior. As for the attitude factor, there was a low level relationship with antibiotic use behavior (p<0.001). There was no relationship between knowledge about antibiotic use or antibiotic resistance and antibiotic use behavior (p>0.05). Therefore, the public should be encouraged to have an proper attitude to use antibiotics correctly and appropriately.